Big data's threat to liberty : surveillance, nudging, and the curation of information - Stra, Henrik Skaug (Academic Press, 2021)
"Big Data permeates all aspects of modern life, and while there is no shortage of potential benefits resulting from this, author Henrik Skaug Stra argues that we must also understand the threats Big Data poses to liberty. The issues discussed in Big Data's Threat to Liberty: Surveillance, Nudging, and the Curation of Information are related to how we are constantly under surveillance. Data is gathered from our homes, our cars, our smartphones, various devices around the house, and public sources such as facial recognition enabled camera surveillance and various websites and social networks. Furthermore, the information gathered is used to influence our actions. Detailed personality profiles are utilized in order to make us purchase products and services, or pay our taxes, through tailor-made nudges aimed at irrational and subconscious mechanisms, and delivered with a level of precision only possible with Big Data-driven algorithmic curation of data. Finally, the information we receive through various media is curated by algorithms, and even people are curated in order to satisfy our desires. By providing us with what the algorithm believes we want, we are spared from the exposure of unpleasant information, and even unpleasant people. The ideological landscapes we traverse are thus characterized by conformity, and a concomitant tyranny of popular opinion becomes ever more coercive as this occurs. The question is: How does being constantly watched, manipulated, and having our world-views shaped as just described affect our freedom? In this book it is argued that Big Data's threat to individual liberty is routinely misunderstood and underappreciated due to (a) vagueness resulting from the concept of liberty being used without it being defined, or (b) the use of definitions based on flawed understandings of what liberty is. In this new and unique contribution to the ethics of Big Data and artificial intelligence, both these challenges are thoroughly addressed."--